The China question great power rivalry and British isolation, 1894-1905 - Otte, Thomas G., 1967- (Oxford University Press, 2007)
Studying the British policy over the 'China Question' from 1894-1905, this text emphasises the connections between European and overseas developments, encompassing diplomatic, commercial financial, and strategic factors as well as the politics of foreign policy.